The Impact of The Labial Flange and Artificial Teeth on Lip Support in Elderly Patients with Maxillary Complete Dentures - Rajali, Aiemeeza; Mustafa, Nor Wati @ Nur Atikah; Zulkiflee, Muhamad Zafir Ashman; Abd Rahman, Ain Najihah; Ahmad, Rohana (Journal of Dentistry Indonesia, 2022)
Both maxillary complete denture’s labial flange and anterior artificial teeth play important roles in re-establish major support for the upper lip of elderly patients. However, whether the labial flange can be removed and still perceived as aesthetic remain unclear. Objective: To determine the perception of young adults toward the effect of a labial flange and anterior teeth on lip support of an elderly with maxillary complete dentures. Methods: A total of 64 young adults were recruited to evaluate the lip support for facial aesthetics of 30 full-face photographs in 3 different states: with an original complete denture (CD), with a flangeless duplicated denture and without the complete denture. They were rated using a Visual Numerical Scale (VNS) of 10, with 1 being the least attractive and 10 being the most attractive and repeated twice in random order. Soft-tissue profile analysis was performed to determine which facial anatomical landmarks were most important for lip support and aesthetics. Results: The overall VNS rating with CD (6.33 ± 0.58) was significantly higher (p < 0.001) than images with flangeless (5.58 ± 1.01) or without CD (5.23 ± 1.30). The landmarks that showed the most significant changes were in the subnasale area and NLA with original CD (p=0.060, p=0.072) and in frontal lip thickness with flangeless (p=0.082). There are strong correlations between subnasale and NLA and the mean total aesthetic VNS rating of images with CD, but not statistically significant (r=0.708; p=0.118, r=-0.835; p=0.078). Conclusion: The labial flange of a maxillary complete denture plays an important role in lip support and results in the aesthetic perception of the dentures wearer. The anterior teeth alone provide fullness to the lips, but not enough for labial support.